2018
DOI: 10.1007/s00405-018-5005-5
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous bone-anchored hearing implant surgery: linear incision technique with tissue preservation versus linear incision technique with tissue reduction

Abstract: LITT-P has a significantly higher rate of skin thickening and LITT-R has a significantly higher proportion of adverse soft tissue reactions. Nevertheless, combined with the advantages of LITT-P described in other studies, this can be advocated as the preferred technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…This likely explains increased failure rate compared to the much shorter follow-up in other studies. [7][8][9][10] Adverse soft tissue reactions recorded in this study (3.9% over the whole follow-up period) were low and compared favourably to those recorded in other studies published, between 2.4%-28%. 3,[7][8][9][10] It is likely that the longer follow-up period reduced the percentage of adverse Holgers' scores recorded in this study, as the majority of adverse Holgers' scores were recorded at one week post-operation.…”
Section: Comparisons With Other Studiessupporting
confidence: 75%
See 2 more Smart Citations
“…This likely explains increased failure rate compared to the much shorter follow-up in other studies. [7][8][9][10] Adverse soft tissue reactions recorded in this study (3.9% over the whole follow-up period) were low and compared favourably to those recorded in other studies published, between 2.4%-28%. 3,[7][8][9][10] It is likely that the longer follow-up period reduced the percentage of adverse Holgers' scores recorded in this study, as the majority of adverse Holgers' scores were recorded at one week post-operation.…”
Section: Comparisons With Other Studiessupporting
confidence: 75%
“…Fixture failure rates reported in other studies have been similarly low [7][8][9] and a recently published case series with a similar number of participants showed a 3% fixture failure rate. 10 Only 1/7 failures in this series was an early failure (before 4 years).…”
Section: Comparisons With Other Studiessupporting
confidence: 57%
See 1 more Smart Citation
“…Van Der Stee et al detected wound dehiscence in 28 implants that had been placed using LT with tissue reduction and 33.7% soft tissue reactions in the same group of patients. In contrast, 27.6% of soft tissue reactions in the LT with tissue preservation group were registered without any wound dehiscence 13 . Furthermore, Badran et al reported that patient satisfaction with skin appearance after tissue removal was not significantly better compared to the cosmetic impact of common hearing aids 14 , 15 .…”
Section: Discussionmentioning
confidence: 77%
“…4,[13][14][15] There has also been a move towards less invasive soft tissue techniques and use of the minimally invasive Ponto surgery technique. [16][17][18][19][20][21][22][23] Many of the previous QoL studies were performed with older devices and using more invasive soft tissue surgical techniques. 24 Whilst it is clear that bone conducting hearing implants demonstrate a qualitative benefit, there remains a paucity of literature comparing pre-and post-operative QoL benefits.…”
Section: Introductionmentioning
confidence: 99%